2011
DOI: 10.4049/jimmunol.1002208
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the NK Cell Immune Synapse Reveal that Activation Thresholds Can Be Established by Inhibitory Receptors Acting Locally

Abstract: NK cell activation is regulated by a balance between activating and inhibitory signals. To address the question of how these signals are spatially integrated, we created a computer simulation of activating and inhibitory NK cell immunological synapse (NKIS) assembly, implementing either a “quantity-based” inhibition model or a “distance-based” inhibition model. The simulations mimicked the observed molecule distributions in inhibitory and activating NKIS and yielded several new insights. First, the total signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 99 publications
(104 reference statements)
2
14
0
Order By: Relevance
“…This assumption is based on the findings that cells with lower level of inhibitory receptors require more inhibitory ligands to achieve the same level of inhibition [9], [10], [12], as the probability of an inhibitory receptor finding its ligand depends on the number of ligands on the target cell (and vice-versa) [11]. We used a sigmoid threshold function (Equation 1), where S denotes the threshold of the NK cell clone in the same experiment, in units of (molecule numbers) 2 as it is given in terms of the MHC*KIR product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is based on the findings that cells with lower level of inhibitory receptors require more inhibitory ligands to achieve the same level of inhibition [9], [10], [12], as the probability of an inhibitory receptor finding its ligand depends on the number of ligands on the target cell (and vice-versa) [11]. We used a sigmoid threshold function (Equation 1), where S denotes the threshold of the NK cell clone in the same experiment, in units of (molecule numbers) 2 as it is given in terms of the MHC*KIR product.…”
Section: Methodsmentioning
confidence: 99%
“…It has been qualitatively shown that murine NK cells with a low level of inhibitory receptors require a higher level of inhibitory ligands to achieve an inhibition of lysis similar to that of cells expressing a high level of receptors [9], [10]. The reason for this may be that the probability of an inhibitory receptor finding its ligand depends on the number of ligands on the target cell (and vice-versa), as shown in our recent study of the dynamics of the NK cell immunological synapse [11]. Similarly, murine NK cells expressing low amounts of Ly49 inhibitory receptors required higher amounts of purified MHC class I protein to inhibit IFN-γ production, than cells expressing high amounts of inhibitory receptors [12].…”
Section: Introductionmentioning
confidence: 99%
“…One can also create hybrid models where different levels of description are modeled using different model types (Shahaf et al, 2008). Many such models of lymphocyte migration or molecular processed were published (e.g., Beltman et al, 2011; Kaplan et al, 2011). A review of ODE, DDE, PDE, stochastic, and ABM models in immunology, including a comparison of their relative advantages and disadvantages, has recently been published (Kim et al, 2009).…”
Section: Mathematical Methods To Analyze and Model Immune System Datamentioning
confidence: 99%
“…The simulation by Kaplan et al (2011) further showed that the concerted motion of receptors in clusters – such as those formed by molecule aggregation on certain membrane microdomains – significantly accelerates the maturation of the NK cell immunological synapse. Membrane microdomains have also been implicated by the study of Mesecke et al The mathematical modeling showed that the association of Src-family kinases with activating but not with inhibitory receptors was essential for the experimentally observed Vav activation (Mesecke et al, 2011).…”
Section: Modeling Nk Cell Signaling Pathways and The Dynamics Of Nk Cmentioning
confidence: 97%
See 1 more Smart Citation